From seed to scale: the impact of innovation on organizational performance in Moroccan Agritech startups - BOUYA Sara; BENDIDI Soukaina; EL KADIRI Kenza (International Journal of Scientific Research and Innovative Studies, 2026)
In Morocco's burgeoning AgriTech sector, innovation emerges as a pivotal lever for organizational performance amid climate volatility and digital disruption. This study rigorously investigates the multifaceted impact of innovation strategies product, process, and digital on key metrics including revenue growth (ROA), operational efficiency, and sustainability indices across 5 case-study startups and a survey of 120 founders/managers (2023-2025). Employing structural equation modeling (PLS-SEM), results confirm a robust pathway (β=0.68, p<0.001, R²=0.52), with digital innovation yielding 32% superior growth versus traditional methods, moderated by ecosystem enablers like incubators (FAO, 2025; Elbahjaoui & Elabjani, 2023). Post-COVID resilience is amplified by AI integration, aligning with Schumpeterian dynamics (Schumpeter, 1934; Teece et al., 1997). Theoretical contributions refine dynamic capabilities for emerging markets; practical implications urge policy reforms for seed funding and skills hubs, positioning Moroccan AgriTech as a North African exemplar (Habibi, 2020; World Bank, 2024). Limitations include regional focus; future work explores longitudinal AI effects. Keywords: Innovation strategies, organizational performance, AgriTech startups, Morocco, digital transformation, dynamic capabilities, PLS-SEM, startup ecosystems. Received Date: December 20, 2025 Accepted Date: January 12, 2025 Published Date: February 01, 2025 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/541